2005
DOI: 10.1007/s00432-005-0677-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the cyclin-dependent kinases inhibitor p27 on resistance of ovarian cancer multicellular spheroids to anticancer chemotherapy

Abstract: Our results implicate that p27 serves as a regulator of drug resistance in ovarian tumors. ASON-mediated alteration of p27 reverses resistance of ovarian cancer to anticancer agents that are associated with increased sensitivity of ovarian cancer cells to chemotherapeutic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…It is supposed that p27 in nucleus binds to cyclin E-CDK2 complex and inactivates the complex in G0/G1 phase, but once p27 is transported to cytosol and degraded, the complex is activated and it triggers the transition from G1 to S phase. Our data were consistent with this kinetics of p27, so it was suggested that intranuclear p27 plays a central role for cellcycle quiescence in sphere forming cells (20)(21)(22).…”
Section: Discussionsupporting
confidence: 90%
“…It is supposed that p27 in nucleus binds to cyclin E-CDK2 complex and inactivates the complex in G0/G1 phase, but once p27 is transported to cytosol and degraded, the complex is activated and it triggers the transition from G1 to S phase. Our data were consistent with this kinetics of p27, so it was suggested that intranuclear p27 plays a central role for cellcycle quiescence in sphere forming cells (20)(21)(22).…”
Section: Discussionsupporting
confidence: 90%
“…However, the 2D monolayer in vitro model does not exhibit the full range of drug resistance observed in in vivo solid tumours. For this reason, three-dimensional (3D) multicellular tumour spheroids (MTS) have been used as an in vitro model of solid tumours for drug resistance studies because they mimic the growth characteristics of in vivo tumours more closely than cancer cell line monolayers (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The acquired MCR has been demonstrated to be linked to a limitation of drug diffusion, to the activation of survival pathways such as NF-κB or mTOR, or to the upregulation of p27 (5)(6)(7)(8)(9). However, the molecular basis of MCR is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, p16 INK4b , p21 Cip1 and p27 Kip1 , whose main function is to induce cell cycle arrest and apoptosis, induce autophagy [16]. p27 Kip1 also can down-regulate P-gp [17]. Thus, enhancement of CKI signaling is particularly noteworthy among the putative molecular targets other than COX-2 in CLX-mediated in vitro antiproliferative effects in cancer cells [13,14].…”
Section: Introductionmentioning
confidence: 99%